Notes on the distribution of Ligularia kingiana (W. W. Sm.) Hand.-Mazz. (Asteraceae): new records - Ирина Дмитриевна Илларионова; С. Дэй; Моаакум (Turczaninowia, 2022)
The Himalayan species Ligularia kingiana (W. W. Sm.) Hand.-Mazz., which for a long time was considered as endemic to the state of Sikkim (India), was first found during field work in the state of Nagaland, almost 700 km from the type locality. The study of herbarium materials and literature revealed that this rare species also occurs in eastern Nepal (Solukhumbu District) and northern Myanmar (Kachin State). For Nepal, L. kingiana is reported for the first time.